Assessment of cytosolic free calcium changes during ceramide-induced cell death in MDA-MB-231 breast cancer cells expressing the calcium sensor GCaMP6m. (June 2018) - Bassett, John J.; Bong, Alice H.L.; Janke, Ellen K.; Robitaille, Mélanie; Roberts-Thomson, Sarah J.; Peters, Amelia A.; Monteith, Gregory R.
Graphical abstract: Highlights: Development of a MDA-MB-231 breast cancer cell line with GCaMP6m stable expression. High content imaging defined [Ca 2+ ]CYT during cell death induced by ceramide. Ceramide induced large [Ca 2+ ]CYT increases and cell death in a subset of cells within 6 h. Morphological changes were not associated with large [Ca 2+ ]CYT increases. Silencing of PMCA1 augmented global [Ca 2+ ]CYT increases and cell death. Abstract: Alterations in Ca 2+ signaling can regulate key cancer hallmarks such as proliferation, invasiveness and resistance to cell death. Changes in the regulation of intracellular Ca 2+ and specific components of Ca 2+ influx are a feature of several cancers and/or cancer subtypes, including the basal-like breast cancer subtype, which has a poor prognosis. The development of genetically encoded calcium indicators, such as GCaMP6, represents an opportunity to measure changes in intracellular free Ca 2+ during processes relevant to breast cancer progression that occur over long periods ( e.g. hours), such as cell death. This study describes the development of a MDA-MB-231 breast cancer cell line stably expressing GCaMP6m. The cell line retained the key features of this aggressive basal-like breast cancer cell line. Using this model, we defined alterations in relative cytosolic free Ca 2+ ([Ca 2+ ]CYT ) when the cells were treated with C2-ceramide. Cell death was measured simultaneously via assessment of propidium iodide permeability. Treatment with ceramide produced delayed and heterogeneous sustained increases in [Ca 2+ ]CYT . Where cell death occurred, [Ca 2+ ]CYT increases preceded cell death. The sustained increases in [Ca 2+ ]CYT were not related to the rapid morphological changes induced by ceramide. Silencing of the plasma membrane Ca 2+ ATPase isoform 1 (PMCA1) was associated with an augmentation in ceramide-induced increases in [Ca 2+ ]CYT and also cell death. This work demonstrates the utility of GCaMP6 Ca 2+ indicators for investigating [Ca 2+ ]CYT changes in breast cancer cells during events relevant to tumor progression, which occur over hours rather than minutes.